Intensi Pembelian Produk Ramah Lingkungan Berdasar Theory of Planned Behaviour - Maharani, Bernadetta Diansepti; Hutami, Lusia Tria Hatmanti; Isna, Kadek (Jurnal Manajemen dan Kewirausahaan, 2021)
This study explains one of the phenomena in Marketing Management, namely the purchasing intention of green products in generation Z. This study uses a modification of the theory development of Theory of Planned Behavior. The purpose of this study was to analyze the effect of attitudes, subjective norms, perceived behavioral control and environmental concern on the purchasing intention of green products in generation Z. The research method used Smart PLS. This study uses a purposive convenience sampling method on 150 college students and students in Yogyakarta who were born between 1995-2012 and know about green products. The research findings indicate that attitudes, subjective norms, perceived behavioral control and environmental concern positively effect on the purchasing intention of green products in generation Z.